The management of HIV in pregnancy: A 10-year experience. (March 2017) - Raffe, Sonia F.; Savage, Charlotte; Perry, Louisa A.; Patel, Amie; Keith, Tricia; Howell, Richard; Bradley, Robert; Bomont, Rob; Fidler, Katy; Gilleece, Yvonne
Abstract: Objective: The package of care to reduce HIV mother to child transmission (MTCT) has evolved significantly since trials of ante and intrapartum antiretroviral therapy (ART) in 1994. In the UK MTCT rate has fallen from 25.6% in the 1990s to 0.46%. We review the management of HIV in pregnancy in Brighton in the context of evolving guidelines. Study design: HIV, obstetric and neonatal notes of all HIV positive women, pregnant between 2003 and 2014, were reviewed. Results: 97 pregnancies in 75 women were identified, resulting in 79 live births. Antenatal HIV diagnosis was made in 22 (28%). The proportion of pregnancies in those with known HIV at conception increased over the time period. At conception 58 (60%) were on ART, 33 (57%) of who continued on their original regimen. 34 (35%) initiated ART following conception: 14 known to be HIV positive, 20 diagnosed during pregnancy. Two did not start ART (1 due to miscarriage, 1 as diagnosed post-delivery) and in three cases ART history was unavailable due to transfer to alternative centres. ART was initiated on average at 22 weeks gestation (range 6–34). 4(5%) received Zidovudine (AZT) monotherapy, all before 2006. Choice of combination ART (cART) varied with time reflecting changing guidelines. Prior to 2008 an AZT containing regimen was used in 83% versus 8% after. Planned mode of delivery was documented in 73: 30(41%) planned a normal vaginal delivery (NVD), 43(59%) a caesarean section (CS). The viral load (VL) was <50 copies/mL in 58(76%) at 36 weeks and 64(84%) at delivery. 90% with a detectable VL at 36 weeks delivered via CS. 100% received neonatal post-exposure prophylaxis (PEP): 68(88%) AZT monotherapy, 9(12%) cART. 84% initiated PEP within four hours. 90% completed 28 days. 8(10%) babies experienced side effects. In the 10-year review period, one infant (1.3%) was diagnosed HIV positive. Both mother and infant received care in accordance with guidelines, including neonatal PEP within 4 hours. Conclusion: Care of the HIV positive pregnant woman in Brighton has been successful with overall transmission consistent with that seen nationally. Despite effective preventative strategies MTCT remains a risk and women should be counselled accordingly.